Racial and Ethnic Minority Pregnant Patients with Low-Income Experiences of Perinatal Care: A Scoping Review (Mary Ann Liebert, 2021)
Purpose: The maternal mortality ratio for the United States (US) has consistently risen over recent decades. This mortality is especially pronounced within minority populations who experience a maternal mortality and morbidity rate that are much higher than their non-Hispanic white counterparts. Qualitative data are critical in gaining true insight from minority pregnant and postpartum persons. Such data should serve as the basis for building interventions and programs that seek to eradicate perinatal inequities. This review examines the qualitative literature on racial and ethnic minority pregnant patients with low income and their experiences during perinatal care (PNC) to identify recurrent themes that can be addressed through targeted interventions. Methods: PubMed, CINAHL, and Web of Science databases were searched for qualitative studies on racial and ethnic minority pregnant patients with low income and their experiences during PNC. Twenty-two articles were included for analysis. Thematic synthesis was performed to identify categories and recurring themes in each article. Results: Five major categories were identified as consistent experiences of pregnant patients with PNC clinicians: support, education, connection, communication, and trust. Of these, clinician support was the most consistently coded category. Eighteen of the 23 articles discussed tangible support patients had received from their clinicians, such as care coordination and referrals to support services. The second most coded category was education, which was represented in 16 articles. Education was mostly represented negatively as lack of adequate perinatal care education given during the perinatal period. Finally, the categories of connection, communication, and trust were represented by 18, 17, and 17 articles, respectively. Conclusions: These qualitative studies provided specific examples of what racial and ethnic minority pregnant patients with low income deemed positive and negative during the perinatal period and outline ways that these experiences can be improved. Future studies can take the experiences reported in this review to help inform interventions to improve patient experiences and health outcomes that minority persons face in the perinatal period.